The annulment of the award due to its reasoning in Peru – how to face a distorted way - Rivas Caso, Gino (2017)
Judicial review of the awards in Peru is in practice problematic and incomprehensible. Even though the law expressly forbids the judicial analysis of the reasoning of the award, in reality more than the half of proceedings for setting aside an award are based on objections to its reasoning. In view of this situation, it is essential to understand which are the “defects” in the reasoning that renders void the award, in order to not commit them. This paper seeks to propose guidelines that allows arbitrators to avoid the annulment of the award due to its reasoning.